Threshold Voltage Control of Multilayered MoS2 Field‐Effect Transistors via Octadecyltrichlorosilane and their Applications to Active Matrixed Quantum Dot Displays Driven by Enhancement‐Mode Logic Gates. Issue 7 (13th January 2019) - Roh, Jeongkyun; Ryu, Jae Hyeon; Baek, Geun Woo; Jung, Heeyoung; Seo, Seung Gi; An, Kunsik; Jeong, Byeong Guk; Lee, Doh C.; Hong, Byung Hee; Bae, Wan Ki; Lee, Jong‐Ho; Lee, Changhee; et al.
Abstract: In recent past, for next‐generation device opportunities such as sub‐10 nm channel field‐effect transistors (FETs), tunneling FETs, and high‐end display backplanes, tremendous research on multilayered molybdenum disulfide (MoS2 ) among transition metal dichalcogenides has been actively performed. However, nonavailability on a matured threshold voltage control scheme, like a substitutional doping in Si technology, has been plagued for the prosperity of 2D materials in electronics. Herein, an adjustment scheme for threshold voltage of MoS2 FETs by using self‐assembled monolayer treatment via octadecyltrichlorosilane is proposed and demonstrated to show MoS2 FETs in an enhancement mode with preservation of electrical parameters such as field‐effect mobility, subthreshold swing, and current on–off ratio. Furthermore, the mechanisms for threshold voltage adjustment are systematically studied by using atomic force microscopy, Raman, temperature‐dependent electrical characterization, etc. For validation of effects of threshold voltage engineering on MoS2 FETs, full swing inverters, comprising enhancement mode drivers and depletion mode loads are perfectly demonstrated with a maximum gain of 18.2 and a noise margin of ≈45% of 1/2 V DD . More impressively, quantum dot light‐emitting diodes, driven by enhancement mode MoS2 FETs, stably demonstrate 120 cd m −2 at the gate‐to‐source voltage of 5 V, exhibiting promising opportunities for future display application. Abstract : Threshold voltage adjustment as a control manner for molybdenum disulfide (MoS2 ) field‐effect transistors (FETs) is demonstrated by back‐channel modification. Octadecyltrichlorosilane treatment on a back channel of MoS2 FETs induces a negative dipole at the interface, leading to depopulation of electrons. As representative applications, active control for one‐pixel quantum dot light‐emitting diode and full‐swing logic gates are successfully demonstrated.